1) The measure needed is the C. Base area, 2) the scenario represents the equation D. 10.5= (1/3)B (4.5)
and 3) the tent will cover C. 7 square feet of the back porch.
Use the appropriate formulas to solve it step-by-step.
We know the height (h) of the conical tent is 4.5 feet.The volume (V) of the tent is given as 10.5 cubic feet.The formula for the volume of a cone is:
[tex]V = \frac{1}{3} \pi r^2 h[/tex]
We need to find the base area of the cone (which is a circle) to determine the area covered by the tent on the back porch. The base area (A) of the cone is:
[tex]A = \pi r^2[/tex]
To calculate this, we must first determine the radius (r) of the cone. Let's rearrange the volume formula to solve for the radius (r):
[tex]10.5 = \frac{1}{3} \pi r^2 4.5[/tex]
Simplifying this equation, we get:
[tex]10.5 = \frac{1}{3} \pi r^2 4.5[/tex]
Multiply both sides by 3 to get rid of the fraction:
[tex]31.5 = \pi r^2 4.5[/tex]
Divide both sides by 4.5:
[tex]\frac{31.5}{4.5} = \pi r^2[/tex]
[tex]7 = \pi r^2[/tex]
Divide both sides by π:
[tex]r^2 = \frac{7}{\pi}[/tex]
Taking the square root of both sides, we find the radius (r):
[tex]r = \sqrt{\frac{7}{\pi}}[/tex]
Now we can calculate the base area (A) of the cone:
[tex]A = \pi r^2[/tex]
Substitute r^2 back into the equation:
[tex]A = \pi \left( \frac{7}{\pi} \right) = 7 \text{ square feet}[/tex]
What is the value of n that makes the expression (-5y + 4) + (7y - 9) equivalent to ny – 5?
Answer:
2
Step-by-step explanation:
If we evaluate (-5y + 4) + (7y - 9), we get 2y - 5.
Therefore, N must equal 2.
I need help with this I will mark brainiest answer if it is correct please help
Answer:
C=40030.17
Step-by-step explanation:
2 x pi x 6371 =40030.17 hope this is what you're looking for :)
Need Help With This Question
Explain your Reasoning Plz!!!!
Answer:
Yes
Step-by-step explanation:
If you have an equalateral triangle with the angle in the bottem left corner, then flip it sideways,right and do the same with the other but, left, it can make a straight angle
|\
| \
| \
| \
| \ I tried my best
|_____\
Answer:
yes
Step-by-step explanation: you can have 2 copies and then add 60 3 times and thats 180 which is what is a straight angle hope this helps god bless
Consider the function.
f(x) = -2/3x-24
Which conclusions can be drawn about f^-1(x)? Select two options.
Answer:
Statement 3
Step-by-step explanation:
y = -2/3x-24
Make x the subject
y + 24 = -(⅔)x
x = -(3/2)(y + 24)
Intersection variables
f^-1(x) = -(3/2)(x + 24)
Slope: -3/2
No domain restrictions
y-intercept: x = 0
-(3/2)(0+24)
-36
(0,-36)
x-intercepts: y = 0
0 = -(3/2)(x + 24)
x = -24
(-24,0)
Linear function, range is all real values of y
Answer:
[tex]f^{-1}(x)\: \textsf{ has a y-intercept of }\:(0,-36)[/tex]
[tex]f^{-1}(x)\: \textsf{ has a range of all real numbers.}[/tex]
Step-by-step explanation:
Given function[tex]f(x)=-\dfrac{2}{3}x-24[/tex]
The given function has an unrestricted domain and range.
Domain: (-∞, ∞) → all real numbersRange: (-∞, ∞) → all real numbersInverse of a function[tex]f^{-1}(x)[/tex] is the notation for the inverse of the function. The inverse of a function is a reflection in the line y = x
Finding the inverse of the given function
Swap f(x) for y:
[tex]\implies y=-\dfrac{2}{3}x-24[/tex]
Rearrange the equation to make x the subject:
[tex]\implies -\dfrac{2}{3}x=y+24[/tex]
[tex]\implies -2x=3y+72[/tex]
[tex]\implies x=-\dfrac{3}{2}y-36[/tex]
Swap the x for [tex]f^{-1}(x)[/tex] and the y for x:
[tex]\implies f^{-1}(x)=-\dfrac{3}{2}x-36[/tex]
The inverse function has a slope of -3/2
The domain of the inverse function is the range of the function.
The range of the inverse function is the domain of the function.
Therefore, the domain and the range are unrestricted.
Domain: (-∞, ∞) → all real numbersRange: (-∞, ∞) → all real numbersThe y-intercept of the inverse function is when x = 0:
[tex]\implies f^{-1}(x)\: \textsf{ has a y-intercept of }\:(0,-36)[/tex]
The x-intercept of the inverse function is when y = 0:
[tex]\implies -\dfrac{3}{2}x-36=0[/tex]
[tex]\implies -\dfrac{3}{2}x=36[/tex]
[tex]\implies x=-24[/tex]
[tex]\implies f^{-1}(x)\: \textsf{ has a x-intercept of }\:(-24,0)[/tex]
Conclusion[tex]f^{-1}(x)\: \textsf{ has a y-intercept of }\:(0,-36)[/tex]
[tex]f^{-1}(x)\: \textsf{ has a range of all real numbers.}[/tex]
can’t figure this out!
[tex]b_n=b_1*q^{n-1}\\b_1=1, q=\frac{3}{1} =3\\b_n=1*3^{n-1}[/tex]
(b and t are the same)
P.S. Hello from Russia
Please solve:
9x-14=9x+1
Step-by-step explanation:
there is no solution for this equation
How can you make 64, multiplying just two numbers?
These are all the answers to this question!
1 x 64 = 64
2 x 32 = 64
4 x 16 = 64
8 x 8 = 64
16 x 4 = 64
32 x 2 = 64
64 x 1 = 64
Answer:
Hope this helps!
Step-by-step explanation:
1 times 64
8 times 8
64 = 1 x 64, 2 x 32, 4 x 16, or 8 x 8. Factors of 64: 1, 2, 4, 8, 16, 32, 64.
220 degrees converted to radians
Answer:
3.83972
Step-by-step explanation:
give me the heart
my answer is correct
Answer:
11 pi/9 radians
Step-by-step explanation:
To convert degrees to radians, multiply by pi/180
220 * pi/180
220pi/180
11 pi/9
can sb please answer this
Answer:
A
Step-by-step explanation:
A line of best fit needs to match the direction of the points and fit in-between the points as much as possible
C is not the right direction
D is not the right direction
B is to the left of the points
What is the degree of the polynomial
T-4t^2+t^3
Answer:
3 degrees.
Step-by-step explanation:
Find the smallest zero of f(x + 5). x =
|| I
Answer:
.
Step-by-step explanation:
3 packages of cheese for $7.17
6 packages of cheese forx dollars
Answer:
$14.34
Step-by-step explanation:
Do 7.17 divided by 3 which is 2.39.
Then multiply that with 6. That is your answer.
what is the answer????
Answer:
[tex](5, 6)[/tex]
Step-by-step explanation:
Step 1: Solve for x in the first equation
[tex]x - y + y = -1 + y[/tex]
[tex]x = y - 1[/tex]
Step 2: Plug in x into the second equation
[tex](y - 1) - 3y = -13[/tex]
[tex]y - 1 - 3y + 1 = -13 + 1[/tex]
[tex]-2y / -2 = -12 / -2[/tex]
[tex]y = 6[/tex]
Step 3: Plug in y into the first equation
[tex]x - (6) + 6 = -1 + 6[/tex]
[tex]x = 5[/tex]
Answer: [tex](5, 6)[/tex]
Answer:
a
Step-by-step explanation:
5/6 minus 1/4 i am too lazy to do it myself
Answer:
Step-by-step explanation:
Answer :5/6 - 1/4 = 7/12 get same denominator and subtract.
Hope this will help u..
find the missing angle.. x=??
Answer: 55°
Step-by-step explanation:
The Angles, 35° and x are equal to a right angle. Right angles are always 90°, which means that 35 + x = 90. Therefore 90°- 35° = 55°.
Answer: 90-35= 55
Step-by-step explanation:
3) An expression containing only numbers is called _ _ _ _ _ _ _ _ _.
Answer:
An expression containing only numbers is called figures
Step-by-step explanation:
Can anyone please help me with this?
1.
20 pounds of strawberries
5 persons
20 ÷ 5 = 20 pounds ÷ 5 persons = 4 pounds per person
Answer: 4 is the pounds per person, how much each person received
2.
20 pounds of strawberries
5 pounds per person
20 ÷ 5 = 20 pounds ÷ 5 pounds/person= 4 persons
Answer: 4 is the number of people we're splitting among
At a pet store, Rhonda paid $11.50 for 3 dog bowls and 4 bones.
Kelly paid $13 for 2 dog bowls and 8 bones. How much will Andrew
pay for 4 dog bowls and 2 bones?
help
Answer:
$8.75
Step-by-step explanation:
Lets put the number of dog bowls as "x" and the number of bones as "y" When we write the equation it comes out like this:
3x+4y=$11.50
2x+8y=$13
Make the "x" equal on both side so we find the lcm of 3 and 2 which 6 so we multiply 2 on the top and 3 on the bottom which changes the equation to
6x+8y=$23
6x+24y=$39 Then we subtract which equals
-16y=-$-13
y=13/16 or 0.8125 we put the "y" on the equation which makes
3x+3.25=11.50 To solve the question: 4(13/16) + 2(2.75)=$8.75 3x=8.25: x= 2.75
Final answer:
Andrew will pay $12 for 4 dog bowls and 2 bones, after calculating the individual prices of the items by setting up and solving a system of equations based on Rhonda's and Kelly's purchases.
Explanation:
To determine how much Andrew will pay for 4 dog bowls and 2 bones, we need to establish the price of a single dog bowl and a single bone. We can do this by setting up two equations based on the transactions made by Rhonda and Kelly.
Let B be the price of one dog bowl and O the price of one bone. Therefore, Rhonda's purchase gives us the equation 3B + 4O = $11.50. Kelly's purchase gives us the equation 2B + 8O = $13.
We can solve this system of equations either by substitution or by the elimination method. In this case, elimination may be more straightforward:
Multiply the first equation by 2, which gives us 6B + 8O = $23.We now subtract Kelly's equation from this, resulting in (6B + 8O) - (2B + 8O) = $23 - $13, simplifying to 4B = $10.Now we know that one dog bowl costs B = $2.50.To find the cost of one bone, we substitute B = $2.50 into either of the original equations. Using Rhonda's equation: 3($2.50) + 4O = $11.50, which simplifies to $7.50 + 4O = $11.50, and further to 4O = $4, meaning O = $1.00.With the prices determined, Andrew's total cost for 4 dog bowls and 2 bones will be 4B + 2O, which equates to 4($2.50) + 2($1.00).Calculating this gives us $10 + $2, which is a total of $12 that Andrew will pay.Jenna was selling muffins and bagels in the lobby to support the math club. Bagels sold for $0.75 and muffins sold for
$1.50. She sold three times as many bagels as muffins and made $112.50 this morning.
Which of the following systems correctly models this situation?
A. 3B-M = 0
10.75 +1.50 M = 112.5
B. B-3M = 112.50
10.75B+1.50M = 0
C. B-3M=0
10.75B +1.50M = 112.50
D. B+3M = 0
10.75B - 1.50M = 112.50
Q: Find the area of the figure shown below and choose the appropriate result.
6 cm
3 cm
3 cm
11 cm
3 cm
3 cm
6 cm
Answer:6cm
Step-by-step explanation:
the answer is
Step-by-step explanation:
18. mark brainliest!
Mrs Lopez drives a number of miles north. Then she drives 34 miles west. She drives 94 miles in all. Complete the number sentences to show how many miles she drives north.
? +_ = _ and _ - _ = ?
Answer:
60
Step-by-step explanation:
number of miles driven north plus 34 equal 94.
subtract 94 from 34 to get your answer.
Mrs. Lopez drives 60 miles north.
The completed number sentences are:
60 + 34 = 94 and 94 - 34 = 60.
What is number sentence?Let's assume Mrs. Lopez drives x miles north.
The number sentence for the total distance she drives can be written as:
x + 34 = 94
This equation represents the sum of the distance she drives north (x) and the distance she drives west (34), which equals the total distance she drives (94).
To find the value of x, subtract 34 from both sides of the equation:
x = 94 - 34
Simplifying the expression, we have:
x = 60
Therefore, Mrs. Lopez drives 60 miles north.
The completed number sentences are:
60 + 34 = 94 and 94 - 34 = 60.
Read on number sentences on https://brainly.com/question/28839703
#SPJ3
Alice and Claire go apple picking. When they are done, Claire has 3 times as many apples in her basket as Alice has in hers. All of the apples are whole. What are the three different possibilities for numbers of apples that could be in the baskets?
Answer:
If Alice has 2, Claire has 6
If Alice has 4, Claire has 12
If Alice has 10, Claire has 30
Step-by-step explanation:
apples = Alice + (Alice x 3)
0.054452 5 .S.F help please and answer please
Answer:
0.054450
Step-by-step explanation:
Since we are to round up to 5 significant figures
Always remember that if there's zero after the decimal point,it means the zero will be neglected
So we will have to take the count from after zero
0.054452
So to round up to 5 SF
0.054450
Geometry
An angle is formed by:
Answer:
An angle is formed by the two rays.Given the three side lengths, how can you tell if a triangle is a right triangle?
Answer:
Square all side lengths. If the longest side length squared is equal to the sum of the squares of the other two side lengths, Then it is a right triangle.
Answer:
Square all side lengths. If the longest side length squared is equal to the sum of the squares of the other two side lengths, Then it is a right triangle.
Step-by-step explanation:
Square all side lengths. If the longest side length squared is equal to the sum of the squares of the other two side lengths, Then it is a right triangle.
Given that,
The three side length should be given. Now in order to prove the triangle is a right triangle. The following information should be considered.The side length should be squared. The longest length side should be squared and equivalent to the sum of the square of the other two side length. Also we called as the pythagoras theorem.Learn more: brainly.com/question/17429689
Chris has 482 comics. He decides to give 94% of them to a friend as a birthday present. How many comics does Chris give away?
Answer:
453 of them
Step-by-step explanation:
if you do 482 times .94, it is 453.
the measure of the arc BC is __.
PLEASE HELP ME WITH THIS QUESTION. ITS URGENT!!!!!!!
The measure of AD = 120 degrees
The measure of arc BC is 40 degrees. If you want the length, it's (2pi/9)(radius)
Answer:
AD=120 degrees
BC=40
Step-by-step explanation:
Marisa wants to buy a new XBOX that costs $300.00. She already saved $25.00 and plans to save an additional $10.00 per week. Write an expression that shows the amount of money Marissa has saved after ANY number of weeks. (Remember no equal sign! )
Answer:
25 + 10x
Step-by-step explanation:
First, add the base $25 from the start.
Next, add $10 per week. The number of weeks is the unknown, and is represented by x, giving 10x.
Put them together, you get 25 + 10x.
Answer:
10x+25
Step-by-step explanation:
The answer is 10x+25 because 25 is the initial value, which is the y intercept. Then, since she saves 10$ per week, it is 10*x, x representing the number of weeks.
Which text feature best indicates that this workplace document is also a procedural document
Answer: b) the numbering
Step-by-step explanation:
the definition of a procedure is “ a series of actions conducted in a certain order or manner”
A full jar of honey weighs 750 grams, and the same jar two-thirds
full weighs 550 grams. What is the weight of the empty jar in grams
Answer:
150 grams
Step-by-step explanation:
The weight of the full jar of honey is equivalent to x + y, where x is equal to the weight of honey and y is equal to the weight of the jar.
x+y = 750
2x/3+y = 550
You can solve for y in the first equation and get:
y = 750-x
Plug that in to the second equation and you get:
-x/3+750 = 550
Subtract 750 from both sides:
-x/3 = -200
Multiple -3 on both sides:
x = 600 grams
The weight of the jar is 750-600 or 150